MEKANISME PASAR DALAM PERSPEKTIF EKONOMI ISLAM - .... ....... (Journal Of Institution And Sharia Finance, 2018)
ABSTRACTIslamic economics views that the market, the state and the individual are in balance (iqtishad), there can be no sub-ordinates, so that one of them becomes dominant over the other. The market is guaranteed freedom in Islam. The free market determines the methods of production and prices, there should be no disturbances that result in the disruption of the market balance. However, because it is difficult to find a market that runs on its own fairly (fairly) and market distortions often occur, so that it can harm the parties, Islam allows for market internevsi by the state to restore the market back to normal. The market, which is allowed to run alone (laissez faire), without anyone controlling it, has actually led to unilateral market control by the capitalist, the infrastructure authority and the information owner. Information asymmetry is also a problem that cannot be solved by the market. The state in Islam has the same role as the market, its job is to regulate and supervise the economy, ensure perfect competition in the market, equitable information and economic justice.The concept of market foodism in Islam can be referred to in the hadith of Rasululllah Saw. Thus, Islam is far ahead of the West in formulating the concept of market mechanisms. The concept of market mechanisms in Islam was further developed scientifically by scholars throughout history, starting from Abu Yusuf, Al-Ghazali, Ibn Taymiyah, Ibn Khaldun, etc. These scholars have discussed the concept of market mechanisms in a comprehensive manner. They have discussed the power of supply and demand. Their study has also reached the factors that influence the market. In an Islamic economy, prices are determined by the forces of supply and demand. If there is a market distortion, the government may intervene in the market. However, Islamic economics is opposed to government intervention with excessive regulations when market forces are free to work to determine competitive prices. Keywords: Mechanism, Market, Economy, Islam  ABSTRAKEkonomi Islam memandang bahwa pasar, negara, dan individu berada dalam keseimbangan (iqtishad), tidak boleh ada sub-ordinat, sehingga salah satunya menjadi dominan dari yang lain.  Pasar dijamin kebebasannya dalam Islam. Pasar bebas menentukan cara-cara produksi dan harga, tidak boleh ada gangguan yang mengakibatkan rusaknya keseimbangan pasar.Tetapi oleh karena sulitnya ditemukan pasar yang berjalan sendiri secara adil (fair) dan distorasi pasar sering terjadi, sehingga dapat merugikan para pihak, maka Islam membolehkan adanya internevsi pasar oleh negara untuk mengembalikan agar pasar kembali normal. Pasar yang dibiarkan berjalan sendiri (laissez faire), tanpa ada yang mengontrol, ternyata telah menyebabkan penguasaan pasar sepihak oleh pemilik modal (capitalist) penguasa infrastruktur dan pemilik informasi. Asymetrik informasi juga menjadi permasalahan yang tidak bisa diselesaikan oleh pasar. Negara dalam Islam mempunyai peran yang sama dengan dengan pasar, tugasnya adalah mengatur dan mengawasi ekonomi, memastikan kompetisi di pasar berlangsung dengan sempurna, informasi yang merata dan keadilan ekonomi.Konsep makanisme pasar dalam Islam dapat dirujuk kepada hadits Rasululllah Saw . Dengan demikian, Islam jauh mendahului Barat dalam merumuskan konsep mekanisme pasar. Konsep mekanisme pasar dalam Islam selanjutnya dikembangkan secara ilmiah oleh ulama sepanjang sejarah, mulai dari Abu Yusuf, Al-Ghazali, Ibnu Taymiyah, Ibnu Khaldun, dsb. Para  ulama tersebut telah membahas konsep mekanisme pasar secara konprehensif. Mereka telah membahas kekuatan supply and demand. Kajian mereka juga telah sampai pada faktar-faktor yang mempengaruhi pasar. Dalam ekonomi Islam harga ditentukan oleh  kekuatan supply and demand.Jika terjadi distorsi pasar maka pemerintah boleh intervensi pasar Namun, ekonomi Islam menentang adanya intervensi pemerintah dengan peraturan yang berlebihan saat kekuatan pasar secara bebas bekerja untuk menentukan harga yang kompetitif.       Kata Kunci : Mekanisme, Pasar, Ekonomi, IslamDAFTAR PUSTAKAAbu Daud, Sunan  No Hadits 3450, jilid III, Dar al-Hadits Syuriah,tt. Al-Assal, A.Muh. dan Abd.Karim,Fathi, “Hukum  Ekonomi Islam” Jakarta:Pustaka Firdaus,1999 Ad-Darimy, Sunan Ad-Darimy, Darul Fikri Beirut , tt. Al-Ghazali, Ihya Ulumuddin, Jilid III. Ash, Shiddiqy,Muhammad Nejatullah, Economic Though of Abu Yusuf,  Aligarh, In Fikri wa Najjar,  vol. 5 No 1, Januari 1964 At-Tirmizy, Al-Jami Shahih Sunan At-Tirmizy, No Hadits 1310, Juz III, Beirut: Dar al-Fikri ,tt, Frank, Robert Frank, Microeconomics and Behavior, 2 nd. Ed, New York: MC Graw Hill, 1994 Green, Marshal, The Economic Theory, terj. Ariswanto, Buku Pintar Teori Ekonomi, Jakarta: Aribu Matra Mandiri, 1997 Hamdani, Ikhwan, Sistem Pasar,  Jakarta: Nurinsani,  2003 Ibnu Taimiyah, Majmu’ Fatawa Ibnu Taymiyah, jilid VIII. -------------------, Al-Hisbah fil Islam, Kairo, Mesir, tt.,Ibnu Khaldun, Muqaddimah, Edisi Indonesia, terj. Ahmadi Taha, Jakarta: Pustaka Firdaus, 2000 ibn Abdur Rahim  Al-Mubarakafuri, Muhammad Abdur Rahman, Tuhfah al-Ahwazy bi Syarah Jami’ At-Tirmizy, Beirut: Darul Kutub al-Ilmiyah, Nomor Hadits 1310 Karim, Adiwarman, Kajian  Ekonomi Islam Kontemporer, Cet.III; Jakarta: 2003 -------------------------, Ekonomi Mikro Islami, Indonesia, The International Insitute of Islamic Thought Cet.III; Indonesia:  2002 Rahman, Rahman,  Economic Doctrines of Islam, Edisi Indonesia,  Doktrin Ekonomi Islam, jilid 4 Terj. Suroyo Nastangin, Dana Bhati Wakaf Yogyakarta: 1996 S.M.Yusuf,  Economic Justice in Islam, Lahore: Muhammad Asyraf, 1971 Smith, Adam  An Inquiry into the Nature and Causes of The Wealth of Nations, New Rochelle,, N.Y : Arlington House, 1966 Yusuf, Abu, Kitab Al-Kharaj, Beirut: Dar al-Ma’arifah, 1979 --------------------------------------------------, The Economic Entreprise in Islam,Islamic Publication, ltd, Lahore, terj. Anas Sidik, Jakarta: Bumi Aksara,2007